Secuencias parciales del gen NS1 de Parvovirus Equino-Hepatitis (EqPV-H) detectados en sueros equinos de Argentina [Conjunto de datos] - Ruiz, Vanesa; Olguin Perglione, Cecilia (Instituto Nacional de Tecnología Agropecuaria (INTA); Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), 2024)
Supplementary datasets to the article "First report of Equine Parvovirus-Hepatitis (EqPV-H) in Argentina". Veterinary journal 306 : 106204. (22 July 2024). Viral sequences were uploaded to the NCBI nucleotide database and are available with the accession numbers PP408676-PP408687